Ascanio I della Corgna and some of his relatives within the documents of his time (with a bibliographic and documentary appendix) - Sabba, Fiammetta (Bibliothecae.it, 2016)
On the occasion of the 500 years since the birth of Ascanio della Corgna (1516) and of his brother Fulvio (1517) a particular biographical picture of the Corgna family is rebuilt through a survey on the archival and bibliographical contemporary documents. The result is an interesting historical, literary, and cultural picture of the Marquis Ascanio, who was a hero of the Battle of Lepanto, and with him of the Della Corgna’s family.